2009
DOI: 10.1074/jbc.m900151200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeabilization by Trypanosome Lytic Factor, a Cytolytic Human High Density Lipoprotein

Abstract: Trypanosome lytic factor (TLF) is a subclass of human high density lipoprotein (HDL) that mediates an innate immune killing of certain mammalian trypanosomes, most notably Trypanosoma brucei brucei, the causative agent of a wasting disease in cattle. Mechanistically, killing is initiated in the lysosome of the target trypanosome where the acidic pH facilitates a membranedisrupting activity by TLF. Here we utilize a model liposome system to characterize the membrane binding and permeabilizing activity of TLF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…As a constituent of HDL 3 particles, it has been assumed, but not demonstrated, that APOL1 participates in cholesterol metabolism. In addition, APOL1 forms ion channels in lipid bilayers 20,21 and may disrupt membranes, 22 but these studies, while informative about APOL1's trypanolytic activity, do not illuminate function within normal cells. Currently, the function of APOL1 in any of the resident cells of the kidney is entirely speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a constituent of HDL 3 particles, it has been assumed, but not demonstrated, that APOL1 participates in cholesterol metabolism. In addition, APOL1 forms ion channels in lipid bilayers 20,21 and may disrupt membranes, 22 but these studies, while informative about APOL1's trypanolytic activity, do not illuminate function within normal cells. Currently, the function of APOL1 in any of the resident cells of the kidney is entirely speculative.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Using 1000 Genomes Project sequence data, 7 two groups demonstrated that coding variants within the neighboring APOL1 gene, 8,9 which is centromeric to MYH9 on 22q12.3, accounted for the association signal. APOL1 is one of six closely related apolipoprotein L family member genes clustered on chromosome 22. APOL1 is restricted to the genomes of humans and some nonhuman primates.…”
mentioning
confidence: 99%
“…Calcein Release Assays-Permeabilization of unilamellar liposomes was assayed as described previously (21). Briefly, liposomes were diluted 1:1000 into 50 mM Tris (pH 7.0), and calcein fluorescence was monitored at 513 nm when excited at 484 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Trypanosome lytic factor (TLF), an HDL subfraction containing apoA-I, apoL-1, and haptoglobin-related protein (HRP), is responsible for the innate killing of susceptible trypanosome parasites (127)(128)(129)(130). The HRP component of TLF binds with high affinity to the cell-surface receptor of the parasite, promoting endocytosis and trafficking of the TLF-parasite particle complex to the lysosome (131)(132)(133)(134). Once contained within the acidified lysosome of the trypanosome, the apoL-1 component of TLF mediates lysosomal rupture and spilling of lysosomal contents into the cytoplasm, effectively killing the trypanosome.…”
Section: Antiinfectious Effectsmentioning
confidence: 99%